The state policy epistemology related to religious moderation: A comparative study of Indonesia and Australia - Abdul Rahim Yunus; Tasbih Hanafiah (EKSPOSE, 2020)
The concept of religious moderation as anti-theses of the spread of various phenomena of religious radicalism in different parts of the world must be developed based on the right epistemological concept. Conceptually, the four epistemological components consisting of source, structure, method and validity with empirical description in both countries namely Indonesia and Australia signal the need to build systemic synergies in each component initiated by the source as its initial foothold, then structure as a construct of its development, then the method as a paradigmatic, procedural and implementing framework, to the extent that the concept of religious moderation can contribute to the strengthening of religious moderation. The alignment of state policy epistemology frameworks related to religious moderation in Indonesia and Australia shows that in the four components of epistemology consisting of sources, structures, methods and validity. At the source, the epistemology of state policy regarding religious moderation in both countries lies in normative theology as well as normative juridical. On structures, the two have structural differences caused by the typology of the communities of the two different countries. In the method, the epistemology of state policy related to religious moderation in both countries lies on intervention and dialogue. While on the validity side, four theories of validity in this case correspondence theory, coherence theory, formative theory, and pragmatic theory can be found in both countries with different dimensions.Konsep moderasi beragama sebagai anti-inisan penyebaran berbagai fenomena radikalisme agama di berbagai belahan dunia harus dikembangkan berdasarkan konsep epistemologis yang tepat. Secara konseptual, keempat komponen epistemologis yang terdiri dari sumber, struktur, metode dan validitas dengan uraian empiris di kedua negara yaitu Indonesia dan Australia menandakan perlunya membangun sinergi sistemik di setiap komponen yang diinisiasi oleh sumber sebagai pijakan awalnya, kemudian struktur sebagai konstruksi pembangunannya, maka metode sebagai paradigmatik, prosedural dan kerangka pelaksanaan, sejauh konsep moderasi beragama dapat berkontribusi pada penguatan Penyelarasan kerangka kerja epistemologi kebijakan negara terkait moderasi beragama di Indonesia dan Australia menunjukkan bahwa dalam empat komponen epistemologi yang terdiri dari sumber, struktur, metode dan validitas. Pada sumbernya, epistemologi kebijakan negara mengenai moderasi beragama di kedua negara terletak pada teologi normatif serta yuridis normatif. Pada struktur, keduanya memiliki perbedaan struktural yang disebabkan oleh tipologi komunitas dari dua negara yang berbeda. Dalam metode tersebut, epistemologi kebijakan negara terkait moderasi beragama di kedua negara terletak pada intervensi dan dialog. Sementara dari sisi validitas, empat teori validitas dalam hal ini teori korespondensi, teori koherensi, teori formatif, dan teori pragmatis dapat ditemukan di kedua negara dengan dimensi yang berbeda.